Influence of Structural Parameters of Arc GrooveK-wire on Bone Drilling - WANG Yi-wen; LOU De-yu; FU Peng-qiang; YAN Ke-pan (Journal of Harbin University of Science and Technology)
In orthopaedic surgery，bone drilling over 55 C will lead to bone tissue necrosis and even oxidation，affecting the effect of surgery. The drilling temperature can be effectively reduced by designing micro-structures such as chip grooves on the tip surface. By choosing Kirschner wire with arc groove for bone drilling experiment， single factor experiment and multi-factor orthogonal experiment method，the influence of structural parameters of Kirschner wire with arc groove ( length of arc groove，depth of arc groove，distance between arc groove and tip) on bone drilling temperature and bone drilling force was studied and the primary and secondary relations were obtained. The prediction model of bone drilling temperature and force is established. The regression equation and coefficient of the empirical model are tested and optimized. The optimal combination of structural parameters is obtained